1999
DOI: 10.1093/humrep/14.3.712
|View full text |Cite
|
Sign up to set email alerts
|

Extremes of body mass do not adversely affect the outcome of superovulation and in-vitro fertilization

Abstract: The effect of extremes of body mass on ovulation is well recognized by clinicians. However, the effect of obesity and extreme underweight on the outcome of in-vitro fertilization (IVF) cycles has received relatively little attention. In a retrospective nested case-control study we examined the effect of the extremes of body mass index (BMI) on IVF-embryo transfer outcome at a university-based IVF unit. A total of 333 patients were included in the study; 76 obese patients (BMI > 27.9) with 152 controls, and 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
3
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(132 citation statements)
references
References 29 publications
12
108
3
9
Order By: Relevance
“…The impact of BMI on assisted reproductive treatments (ART), such as IVF and ICSI is conflicting, with some studies showing no effect [14], and others demonstrating a poor pregnancy outcome with a higher BMI. Two large meta-analyses looking at the impact of BMI on IVF outcomes found insufficient evidence to draw firm conclusions on the impact of BMI on live birth rate [15] …”
Section: Bmi and Ivf/icsimentioning
confidence: 99%
“…The impact of BMI on assisted reproductive treatments (ART), such as IVF and ICSI is conflicting, with some studies showing no effect [14], and others demonstrating a poor pregnancy outcome with a higher BMI. Two large meta-analyses looking at the impact of BMI on IVF outcomes found insufficient evidence to draw firm conclusions on the impact of BMI on live birth rate [15] …”
Section: Bmi and Ivf/icsimentioning
confidence: 99%
“…The association between obesity and miscarriage has been reported in a number of studies, both in the general population (38) as well as in women undergoing assisted reproductive techniques (ART) (39,40). A remarkable number of these studies show an increase in the prevalence of miscarriage in case of obesity (38,(41)(42)(43); however, there are studies that found no association between these two issues (40,44).…”
Section: Obesity and Miscarriagementioning
confidence: 99%
“…A remarkable number of these studies show an increase in the prevalence of miscarriage in case of obesity (38,(41)(42)(43); however, there are studies that found no association between these two issues (40,44). The link between obesity and miscarriage has been reported in both natural and assisted conceptions.…”
Section: Obesity and Miscarriagementioning
confidence: 99%
“…Obesity is often seen as potentially treatable threat to the success of assisted reproduction, and while patients are commonly advised to try to normalize their weight before undertaking in vitro fertilization (IVF), many find weight loss difficult (1). Couples with infertility often wonder whether lifestyle habits might compromise their ability to reproduce.…”
Section: Introductionmentioning
confidence: 99%